Alanine Scan of α-Conotoxin RegIIA Reveals a Selective α3β4 Nicotinic Acetylcholine Receptor Antagonist - Kompella, Shiva N. (J Biol Chem, 2015)
Activation of the α3β4 nicotinic acetylcholine receptor (nAChR) subtype has recently been implicated in the pathophysiology of various conditions, including development and progression of lung cancer and in nicotine addiction. As selective α3β4 nAChR antagonists, α-conotoxins are valuable tools to evaluate the functional roles of this receptor subtype. We previously reported the discovery of a new α4/7-conotoxin, RegIIA. RegIIA was isolated from Conus regius and inhibits acetylcholine (ACh)-evoked currents mediated by α3β4, α3β2, and α7 nAChR subtypes. The current study used alanine scanning mutagenesis to understand the selectivity profile of RegIIA at the α3β4 nAChR subtype. [N11A] and [N12A] RegIIA analogs exhibited 3-fold more selectivity for the α3β4 than the α3β2 nAChR subtype. We also report synthesis of [N11A,N12A]RegIIA, a selective α3β4 nAChR antagonist (IC(50) of 370 nm) that could potentially be used in the treatment of lung cancer and nicotine addiction. Molecular dynamics simulations of RegIIA and [N11A,N12A]RegIIA bound to α3β4 and α3β2 suggest that destabilization of toxin contacts with residues at the principal and complementary faces of α3β2 (α3-Tyr(92), Ser(149), Tyr(189), Cys(192), and Tyr(196); β2-Trp(57), Arg(81), and Phe(119)) may form the molecular basis for the selectivity shift.